Facile synthesis of CuO micro-sheets over Cu foil in oxalic acid solution and their sensing properties towards n-butanol. Issue 5 (8th January 2016) - Dong, Chengjun; Wang, Lihong; Chen, Gang; Xiao, Xuechun; Djerdj, Igor; Wang, Yude
Abstract : Here, CuO micro-sheets were successfully synthesized from Cu foil using the annealing procedure. Abstract : Here, CuO micro-sheets were successfully synthesized from Cu foil using the annealing procedure. Cupric oxalate (CuC2 O4 · x H2 O) micro-sheets were firstly peeled off by immersing Cu foil in oxalic acid solution at room temperature, and then they were converted into CuO with preserved configuration after thermal treatment at 350 °C. Various techniques were employed for the characterization of the structure and morphology of as-prepared products. Results revealed that the samples were composed of a large amount of porous CuO micro-sheets, which were constructed by plenty of nano-sized primary particles. A gas sensor was fabricated using as-prepared CuO micro-sheets and was systematically investigated for its ability to detect n -butanol. Due to the porous structure of CuO micro-sheets, the sensor based on CuO micro-sheets manifests a remarkably improved sensing performance, including high response, good selectivity, excellent reproducibility and stability, and limit of detection as low as 10 ppm at 160 °C, suggesting its greatly promising applications in gas sensing.